ANALISIS PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TEMA “KEARIFAN LOKAL” DI KELAS V MI ROUDLOTUT THOLIBIN WARUKULON PUCUK LAMONGAN - Nurfarikha, Atika; Nikmah, Khoirotun; Sa’adah, Hurin Innihayatus (-, 2025)
This independent curriculum is commensurate or in accordance with Ki Hajar Dewantara's thoughts. Because in this curriculum learning is student-centered, and the teacher is the facilitator. With this, the researcher analyzed the application of P5 local wisdom themes at MI Roudlotut Tholibin Warukulon with the aim of 1) To find out the application of P5 local wisdom themes at MI Roudlotut Tholibin Warukulon, especially in class V. 2) To find out what factors hinder and support the implementation of P5 the theme of local wisdom at MI Roudlotut Tholibin Warukulon, especially class V. This research uses field research with a qualitative approach. From this research, it can be seen that the application of the P5 theme of local wisdom has supported the success of the target to achieve learning objectives, namely by carrying out real action activities such as practicing traditional games which will then encourage students to work together and get reacquainted with the culture of our region.